The cost-effectiveness of dulaglutide versus liraglutide for the treatment of type 2 diabetes mellitus in Spain in patients with BMI ≥30 kg/m2. (4th May 2017) - Dilla, Tatiana; Alexiou, Dimitra; Chatzitheofilou, Ismini; Ayyub, Ruba; Lowin, Julia; Norrbacka, Kirsi
Abstract: Objective: Dulaglutide 1.5 mg once weekly is a novel glucagon-like peptide 1 (GLP-1) receptor agonist, for the treatment of type two diabetes mellitus (T2DM). The objective was to estimate the cost-effectiveness of dulaglutide once weekly vs liraglutide 1.8 mg once daily for the treatment of T2DM in Spain in patients with a BMI ≥30 kg/m 2 . Methods: The IMS CORE Diabetes Model (CDM) was used to estimate costs and outcomes from the perspective of Spanish National Health System, capturing relevant direct medical costs over a lifetime time horizon. Comparative safety and efficacy data were derived from direct comparison of dulaglutide 1.5 mg vs liraglutide 1.8 mg from the AWARD-6 trial in patients with a body mass index (BMI) ≥30 kg/m 2 . All patients were assumed to remain on treatment for 2 years before switching treatment to basal insulin at a daily dose of 40 IU. One-way sensitivity analyses (OWSA) and probabilistic sensitivity analyses (PSA) were conducted to explore the sensitivity of the model to plausible variations in key parameters and uncertainty of model inputs. Results: Under base case assumptions, dulaglutide 1.5 mg was less costly and more effective vs liraglutide 1.8 mg (total lifetime costs €108, 489 vs €109, 653; total QALYS 10.281 vs 10.259). OWSA demonstrated that dulaglutide 1.5 mg remained dominant given plausible variations in key input parameters. Results of the PSA were consistent with base case results. Limitations: Primary limitations of the analysis are common to other cost-effectiveness analyses of chronic diseases like T2DM and include the extrapolation of short-term clinical data to the lifetime time horizon and uncertainty around optimum treatment durations. Conclusion: The model found that dulaglutide 1.5 mg was more effective and less costly than liraglutide 1.8 mg for the treatment of T2DM in Spain. Findings were robust to plausible variations in inputs. Based on these results, dulaglutide may result in cost savings to the Spanish National Health System.